Associations of polymorphisms in IL-6 and IL-18 with tuberculosis: Evidence from a meta-analysis. (February 2020) - He, Chenyan; Liu, Li
Abstract: Background: Associations between polymorphisms in interleukin-6 ( IL-6 )/interleukin-18 ( IL-18 ) and tuberculosis (TB) were already reported by many publications. The aim of this meta-analysis was to better clarify associations between polymorphisms in IL-6/IL-18 and TB by combing the results of all relevant publications. Methods: Eligible publications were searched from Pubmed, Embase, WOS and CNKI. We used Review Manager to combine the results of individual studies. Results: Twenty-five studies were included in this study. IL-6 rs1800795 (dominant comparison: OR 1.43, 95% CI 1.23–1.67; recessive comparison: OR 0.48, 95% CI 0.35–0.65; allele comparison: OR 1.43, 95% CI 1.27–1.62), IL-18 rs1946518 (dominant comparison: OR 1.19, 95% CI 1.04–1.35; recessive comparison: OR 0.82, 95% CI 0.71–0.96; allele comparison: OR 1.14, 95% CI 1.05–1.24) and IL-18 rs187238 (dominant comparison: OR 1.35, 95% CI 1.15–1.58; allele comparison: OR 1.31, 95% CI 1.14–1.50) polymorphisms were all significantly associated with TB in the total population. Subgroup analyses showed that positive findings for rs1946518, rs187238 and rs1800795 polymorphisms were mainly driven by the Asians. Conclusions: Collectively, this meta-analysis proved that IL-6 rs1800795, IL-18 rs1946518 and IL-18 rs187238 polymorphisms may confer susceptibility to TB, especially for Asians. Highlights: This is a comprehensive meta-analysis about IL-6/IL-18 polymorphisms and TB. We found that IL-6 rs1800795 polymorphism may confer susceptibility to TB. We found that IL-18 rs1946518 and rs187238 polymorphisms may confer susceptibility to TB.